Effects of chronic stress on the brain - the evidence from morphological examinations of hippocampus in a chronic unpredictable stress (CUS) model in rats - Joanna Sekita-Krzak; Iwona Żebrowska-Łupina; Tomasz Łupina; Leszek Czajkowski; Beata Cichacz-Kwiatkowska; Joanna Robaczewska (Kazimierz Wielki University, 2016)
Sekita-Krzak Joanna, Żebrowska-Łupina Iwona, Łupina Tomasz, Czajkowski Leszek, Cichacz-Kwiatkowska Beata, Robaczewska Joanna. Effects of chronic stress on the brain - the evidence from morphological examinations of hippocampus in a chronic unpredictable stress (CUS) model in rats. Journal of Education, Health and Sport. 2016;6(12):384-399. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.203269 http://ojs.ukw.edu.pl/index.php/johs/article/view/4068         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 754 (09.12.2016). 754 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 12.12.2016. Accepted: 14.12.2016.       Effects of chronic stress on the brain - the evidence from morphological examinations of hippocampus in a chronic unpredictable stress (CUS) model in rats   Joanna Sekita-Krzak1, Iwona Żebrowska-Łupina2, Tomasz Łupina3, Leszek Czajkowski2, Beata Cichacz-Kwiatkowska1, Joanna Robaczewska4 1 Department of Histology and Embryology with the Lab of Experimental Cytology, Medical University, Lublin, Poland 2 Department of Clinical Pharmacology, Medical University, Lublin, Poland 3 Department of Pulmonology, Oncology and Allergology, Medical University, Lublin, Poland 4 Department of  Public Health, Collegium Medicum UMK, Poland         Abstract Background. Chronic stress exposure deteriorates memory and increases the risk of psychiatric disorders, including depression. Objectives. The objective of this study was to perform morphological studies in experimental model of neuropsychiatric disorder and to assess histologically the effect of chronic unpredictable stress procedure (CUS) influence on hippocampus. Material and methods. Chronic unpredictable stress procedure (CUS) was applied for 8 weeks in rats by the modified method described by Katz et al. Experimental model of neuropsychiatric disorder was used based on morphological studies of hippocampal formation. Results. Stress-induced alterations were observed in the hippocampus. Nerve cell changes included  neuron shrinkage and dendritic remodeling. The most vulnerable hippocampal cells to chronic stress were CA3 and CA4 pyramidal neurons. In dentate gyrus chronic stress led to granule neuron shrinkage and slight exacerbation of apoptosis in the polygonal cell layer. CUS led to statistically significant changes in quantitative characteristics of the CA3 and CA4 neuron size and nuclei diameter. Conclusions. Chronic stress induces degeneration of hippocampal neurons. The observed neuronal changes indicate the damage of the neurons did not involve neither apoptosis nor necrosis Similarity between histological changes obtained in 8-week long CUS procedure applied in our research and morphological changes described in depressed patients confirms the usefulness of the applied stress procedure as the experimental model of depression.   Key words: stress, depression, hippocampus, chronic unpredictable stress procedure (CUS), animal model, morphology.